THE EXECUTION INSTANCE OF THE JUDICIAL JUDGEMENTS SENTENCED IN THE LITIGATIONS OF ADMINISTRATIVE CONTENTIOUS - ADRIANA ELENA BELU; ANDREEA DIANA PAPA (Challenges of the Knowledge Society)
The instance which solved the fund of the litigation rising from an administrative contract differs depending on the material competence sanctioned by law, in contrast to the subject of the commercial law where the execution instance is the court. In this matter the High Court stated in a decision1 that in a first case the competence of solving the legal contest against the proper forced execution and of the legal contest that has in view the explanation of the meaning of spreading and applying the enforceable title which does not proceed from a jurisdiction organ is in the authority of the court. The Law of the Administrative Contentious no 554/2004 defines in Article 2 paragraph 1 letter t) the notion of execution instance, providing that this is the instance which solved the fund of the litigation of administrative contentious, so even in the case of the administrative contracts the execution instance is the one which solved the litigation rising from the contract. Corroborating this disposal with the ones existing in articles 22 and 25 in the Law, it can be shown that no matter the instance which decision is an enforceable title, the execution of the law will be done by the instance which solved the fund of the litigation regarding the administrative contentious.